Insulin-increased L-arginine transport requires A(2A) adenosine receptors activation in human umbilical vein endothelium. - Enrique Guzmán-Gutiérrez (PLoS ONE, 2012)
Adenosine causes vasodilation of human placenta vasculature by increasing the transport of arginine via cationic amino acid transporters 1 (hCAT-1). This process involves the activation of A(2A) adenosine receptors (A(2A)AR) in human umbilical vein endothelial cells (HUVECs). Insulin increases hCAT-1 activity and expression in HUVECs, and A(2A)AR stimulation increases insulin sensitivity in subjects with insulin resistance. However, whether A(2A)AR plays a role in insulin-mediated increase in L-arginine transport in HUVECs is unknown. To determine this, we first assayed the kinetics of saturable L-arginine transport (1 minute, 37°C) in the absence or presence of nitrobenzylthioinosine (NBTI, 10 µmol/L, adenosine transport inhibitor) and/or adenosine receptors agonist/antagonists. We also determined hCAT-1 protein and mRNA expression levels (Western blots and quantitative PCR), and SLC7A1 (for hCAT-1) reporter promoter activity. Insulin and NBTI increased the extracellular adenosine concentration, the maximal velocity for L-arginine transport without altering the apparent K(m) for L-arginine transport, hCAT-1 protein and mRNA expression levels, and SLC7A1 transcriptional activity. An A2AAR antagonist ZM-241385 blocked these effects. ZM241385 inhibited SLC7A1 reporter transcriptional activity to the same extent in cells transfected with pGL3-hCAT-1(-1606) or pGL3-hCAT-1(-650) constructs in the presence of NBTI + insulin. However, SLC7A1 reporter activity was increased by NBTI only in cells transfected with pGL3-hCAT-1(-1606), and the ZM-241385 sensitive fraction of the NBTI response was similar in the absence or in the presence of insulin. Thus, insulin modulation of hCAT-1 expression and activity requires functional A(2A)AR in HUVECs, a mechanism that may be applicable to diseases associated with fetal insulin resistance, such as gestational diabetes.